Accuracy of diagnostic codes for identifying patients with ulcerative colitis and Crohn’s disease in the Veterans Affairs Health Care System. - Hou, JK (Dig Dis Sci, 2014)
BACKGROUND: International Classification of Diseases-9 (ICD-9) codes are useful in clinical research; however, the validity of ICD-9 codes for inflammatory bowel disease (IBD) patients in multiple centers in the Veterans Affairs Health Care Systems (VA) has not been established. Our aim was to determine the accuracy of ICD-9 codes for Crohn’s disease (CD) and ulcerative colitis (UC) in the VA. METHODS: Patients with a diagnosis of IBD during 1999–2009 were identified by at least one ICD-9 code for CD (555.x) or UC (556.x) at the Houston and Ann Arbor VA Medical Centers and confirmed by chart review. A diagnosis of CD, UC, and IBD, unspecified (IBDU) was determined based on structured review of data in the VA medical records. Positive predictive values (PPV) were calculated for the codes using previously published ICD-9 algorithms. RESULTS: A total of 1,871 patients were identified with ICD-9 codes for IBD. Of these patients, 1,298 (69 %) were confirmed to have IBD, with 541 CD (41 %), 707 UC (55 %), and 50 IBDU (4 %) patients. An algorithm of 2 or more codes with at least one from an outpatient encounter improved the PPV (0.83 and 0.89 for CD and UC, respectively) compared a single code algorithm (PPV 0.59 and 0.66, respectively). CONCLUSION: Single ICD-9 codes are inadequate to accurately define IBD patients; however, ICD-9 code algorithms can be used to identify patients with UC or CD with high positive predictive value. The 2 code, at least 1 outpatient code algorithm was observed to have a high PPV and low miss rate.